Analysis of multiphase flow simulations and comparison with high-speed video observations. (December 2021) - Schmelter, Sonja; Olbrich, Marc; Knotek, Stanislav; Bär, Markus
Abstract: Computational fluid dynamics (CFD) can help to improve the metrological characterization of multiphase flows by giving insight into areas that are hardly accessible by experiments. In this paper, simulation results for seven different plug and slug flow test cases are presented. Liquid level time series are compared with corresponding experimental data that have been derived from high-speed video observations of the flow pattern. These data allow a quantitative comparison between simulation and experiment with respect to relevant flow characteristics, such as mean liquid level or slug frequency.